Myeloid-derived growth factor promotes M2 macrophage polarization and attenuates Sjögren’s syndrome via suppression of the CX3CL1/CX3CR1 axis - Yang, Zi; Liu, Mangnan; Chang, Zhichao; Du, Conglin; Yang, Yang; Zhang, Chen; Hu, Liang (Frontiers in Immunology, 2024)
Introduction: Primary Sjögren syndrome (pSS) is a systemic autoimmune disease that is characterized by the inﬁltration of immune cells into the salivary galands. The re-establishment of salivary gland (SG) function in pSS remains a clinical challenge. Myeloid-derived growth factor (MYDGF) has anti-inflammatory, immunomodulatory, and tissue-functional restorative abilities. However, the potential of MYDGF to restore salivary glands (SGs) function during pSS has not yet been investigated. Methods: Non-obese diabetic (NOD)/Ltj mice (pSS model) were intravenously administered with adeno-associated viruses of MYDGF at 11 weeks of age. Salivary flow rates were determined before and after treatment. Mice were sacrificed 5 weeks after MYDGF treatment, and submandibular glands were collected for analyses of histological disease scores, inflammatory cell infiltration, PCR determination of genes, and western blotting of functional proteins. Furthermore, mRNA sequencing and bioinformatics predicted the mechanism of the therapeutic effect of MYDGF. Results: Treatment of NOD/Ltj mice with MYDGF alleviated pSS, as indicated by the increased salivary flow rate, reduced lymphocyte infiltration, attenuated glandular inflammation, and increased AQP5 and NKCC1 expression. The gene expression of cytokines and chemokines, such as Ccl12, Ccl3, Il1r1, Ccr2, Cx3cr1, Il7, Mmp2, Mmp14, Il1b, and Il7, significantly decreased after treatment with MYDGF, as determined by RNA sequencing. Meanwhile, MYDGF inhibits infiltration of macrophages (Mϕ) in SGs, induces polarization of M2ϕ, and suppresses C-X3C motif ligand 1 (CX3CL1)/C-X3C motif receptor 1 (CX3CR1) axis. Conclusions: Our findings showed that MYDGF could revitalize the SG function of pSS, inhibit infiltration of Mϕ, and promote M2ϕ polarization via suppression of the CX3CL1/CX3CR1 axis, which has implications for potential therapy for pSS.